Pelaksanaan Pelayanan Publik di Kantor Kecamatan Sungai Kunjang Kota Samarinda - Muhammad Syarif Aziz; Muhammad Jamal Amin; Iman Surya (Jurnal Ilmu Pemerintahan, 2023)
The purpose of this study was to find out how the implementation of public services was implemented at the Sungai Kunjang District Office, Samarinda City and what were the inhibiting factors in the implementation of public services at the Sungai Kunjang District Office, Samarinda City. Service is the essential main task of the figure of the apparatus, as a servant of the state and a servant of society. The government has an important role to provide excellent public services for all citizens. Along with the implementation of the regional autonomy policy, government bureaucracy officials in the regions can manage and provide public services that are more concerned with the needs of their local communities. Based on the results of research conducted at the Sungai Kunjang District Office, Samarinda City, the implementation of public services by the Sungai Kunjang District Office, Samarinda City, is in a fairly good category. inhibiting factors in the implementation of public services at the Sungai Kunjang District Office, Samarinda City, namely: lack of work discipline such as problems of late working time and completion of work, lack of service transparency and outreach to the community, lack of employee ability to carry out the tasks assigned to them and lack of employee awareness of responsibilities. Abstract made in Indonesian.